Extended electronic structure inhomogeneity created by double chain layer defects surrounding columnar tracks in heavy-ion irradiated YBa2Cu3O7−δ. (31st August 2018) - Kwon, Ji-Hwan; Meng, Yifei; Wu, Lijun; Zhu, Yimei; Zhang, Yifei; Selvamanickam, Venkat; Welp, Ulrich; Kwok, Wai-Kwong; Zuo, Jian-Min
Abstract: In YBa2 Cu3 O7− δ (YBCO), heavy-ion irradiation creates continuous amorphous tracks that are highly effective for vortex pinning. However, the electronic structure landscape of defects and consequently their vortex pinning roles are unclear. Here, we show double chain layer (DCL) defects which intersect the columnar tracks are additionally produced by high energy Pb ion irradiation in YBCO. The DCL defects are ∼29 nm long, about three times the columnar defect diameter. The electronic structures of the DCL and columnar track defects were determined using atomic-resolution scanning transmission electron microscopy (STEM) and high resolution electron energy loss spectroscopy (EELS). Results show a decrease in the oxygen and copper content at the interface between the track and the YBCO matrix, resulting in interfacial strain. For the DCL defects, the STEM/EELS study revealed a localized electron doped CuO2 plane next to the DCL defect. The DCL defects thus further extend the electronic inhomogeneity into YBCO.